6th International Immunoglobulin Symposium: Poster presentations - Fernandez-Cruz, E (Blackwell Science Inc, 2009)
The posters presented at the 6th International Immunoglobulin Symposium covered a wide range of fields and included both basic science and clinical research. From the abstracts accepted for poster presentation, 12 abstracts were selected for oral presentations in three parallel sessions on immunodeficiencies, autoimmunity and basic research. The immunodeficiency presentations dealt with novel, rare class-switch recombination (CSR) deficiencies, attenuation of adverse events following IVIg treatment, association of immunoglobulin (Ig)G trough levels and protection against acute infection in patients with X-linked agammaglobulinaemia (XLA) and common variable immunodeficiency (CVID), and the reduction of class-switched memory B cells in patients with specific antibody deficiency (SAD). The impact of intravenous immunoglobulin on fetal alloimmune thrombocytopenia, pregnancy and postpartum-related relapses in multiple sclerosis and refractory myositis, as well as experiences with subcutaneous immunoglobulin in patients with multi-focal motor neuropathy, were the topics presented in the autoimmunity session. The interaction of dendritic cell (DC)-SIGN and α2,6-sialylated IgG Fc and its impact on human DCs, the enrichment of sialylated IgG in plasma-derived IgG, as wells as prion surveillance and monitoring of anti-measles titres in immunoglobulin products, were covered in the basic science session. In summary, the presentations illustrated the breadth of immunoglobulin therapy usage and highlighted the progress that is being made in diverse areas of basic and clinical research, extending our understanding of the mechanisms of immunoglobulin action and contributing to improved patient care.